Antiulcerogenic Activity of Vitamin E on Gastric Ulcers produced by Indomethacin - Ayesha Yousaf, Ifra Saeed, Tehzeeb ul Hassan, Rana Fahd Intisar, Mohammad Amin Shiekh, Ayesha Yousaf, Ifra Saeed, Tehzeeb ul Hassan, Rana Fahd Intisar, Mohammad Amin Shiekh (Journal of Rawalpindi Medical College, 2021)
Objective: To study the morphological and histological effects of vitamin E on gastric lesions produced by indomethacin. Materials and Methods: This was an animal interventional study, 48 adult healthy albino mice were selected and were split into four groups A, B, C and D. Number of animals in each group was 12. Group A was categorized as control. Evion 400mg/kg was administered to Group B. Indocid 25mg/kg was given to group C. Indocid and Evion both (25mg/kg &400 mg/kg respectively) were administered to Group D. In all group, six animals were selected and treated for three days and rest for eight days with calculated doses of drugs. Mice were sacrificed and dissection was done 24 hours after the last dose. The stomach was identified, washed, and observed under dissecting microscope to study the number and shape of ulcers. The dimension of ulcers was measured under a compound microscope. Results: No ulcers were seen in groups A and B. 35 and 10 ulcers were observed in groups C and D respectively. The mean number of ulcers in groups C and D was statistically significant (p-value=0.000). In comparison to group D, Pindot, linear, Irregular, and punched-out ulcers were more prevalent in group C and were statistically significant (p-value < 0.05). The mean linear dimension of ulcers in group C was much greater than in group D. The mean dimension of ulcers in group C1 and C2 was 262.50µm and 232.5µm respectively. Whereas in group D1 and D2 given both Indocid and vitamin E the dimensions were 56.5µm and 50µm. Conclusion: Vitamin E has an anti-ulcerogenic effect on stomach mucosa by reducing the number and dimension of ulcers.